Harnessing microalgae for finfish nutrition: advances in biotechnology and aquafeed development - Justin Tierney; Peter J. Ralph; Igor Pirozzi; Mathieu Pernice (Frontiers in Marine Science)
Finfish aquaculture is a key contributor to global seafood production, providing quality protein to consumers across the world, however, the search for regenerative, cost-effective and scalable raw materials continues. Alternatives to wild-caught fish have been explored extensively with limited success. Among the most promising alternatives is autotrophic marine microalgae as they produce essential fatty acids, amino acids and bioactive compounds that support fish growth and immune function. However, their development into aquafeed is limited due to cost. By considering the major benefits of microalgae in aquafeed, as well as biotechnological advancements in the industry, this review aims to consolidate multi-disciplinary findings and highlight research opportunities to facilitate widespread adoption of microalgae into aquafeed.